3rd European Quality of Life Survey Quality of life in Europe : subjective well-being - Eiffe, Franz; Abdallah, Saamah; Stoll, Laura; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2012)
How can data on subjective well-being - how people perceive the quality of their lives - be used in policy? And are such data relevant in the context of the economic challenges that Europe is currently facing? This report draws out new policy-relevant findings from the third wave of Eurofound's European Quality of Life Survey (EQLS), conducted in 2011-2012. It shows how data on well-being can help policymakers identify the groups and countries that are bearing the brunt of the economic crisis, as well as those that are holding out better than expected, and provides a new layer of evidence to aid policy decisions.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Social surveys -- European Union countries; Quality of life -- European Union countries; Europe -- Social conditions -- 21th century; Electronic books